Annie Leibovitz : [videorecording (DVD)] : life through a lens - Leibovitz, Barbara (Warner Home Video, 2008)
An in-depth look at one of the most well-known photographers in the 21st century. From her childhood to her life at Rolling Stone and Vanity Fair, and her relationships throughout it all. Includes interviews with her subjects and Leibovitz herself.